2019
DOI: 10.1111/joca.12267
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy, Health Numeracy, and Trust in Doctor: Effects on Key Patient Health Outcomes

Abstract: This research examines the roles of health literacy, health numeracy, and trust in doctor on: (1) patient anxiety when consulting a doctor; (2) frequency of physician consultations; and (3) patient subjective well‐being (SWB). Our sample consisted of 4,040 adults representative of the United States in terms of age, income, and education, but equally split among White/Caucasian (50%) and Black/African American (50%) respondents. We found that functional and communicative health literacy and trust in doctor have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 67 publications
(172 reference statements)
0
38
0
Order By: Relevance
“…A person's literacy level impacts their health literacy levels and their overall health outcomes. Studies show that a person's literacy level has a direct effect on their ability to understand health information, their knowledge of health service availability, their decision-making capability, their anxiety level during physician consultation, and their adherence to medications and other treatment protocols [18]. In order for public health and healthcare to implement successful responses to infectious disease outbreaks, the population needs to be able to understand the information that is being presented to them, follow health instructions and guidance, and ultimately adopt the prevention behaviors recommended.…”
Section: Other Subgroups Of Plhivmentioning
confidence: 99%
“…A person's literacy level impacts their health literacy levels and their overall health outcomes. Studies show that a person's literacy level has a direct effect on their ability to understand health information, their knowledge of health service availability, their decision-making capability, their anxiety level during physician consultation, and their adherence to medications and other treatment protocols [18]. In order for public health and healthcare to implement successful responses to infectious disease outbreaks, the population needs to be able to understand the information that is being presented to them, follow health instructions and guidance, and ultimately adopt the prevention behaviors recommended.…”
Section: Other Subgroups Of Plhivmentioning
confidence: 99%
“…2 Research shows that lack of trust in the patient-clinician relationship can lead to patient disempowerment, less treatment adherence, and worse health outcomes. 17,18,19 Moreover, on average, physicians spend less time with Black patients. One study that found that the average length of psychiatric clinic visits with African Americans was several minutes shorter than visits with White patients.…”
Section: Historicizing the History And Physicalmentioning
confidence: 99%
“…These dimensions are known to be important antecedents, mediators, and moderators for important humanistic outcomes and behaviors [38]. For instance, in the health context, health literacy is a subjective reflection of one's "knowledge pertaining to health care issues" [45]. The trust in doctors that patients place and anxiety visiting doctors are additional examples of health-related psychometric dimensions [22,54].…”
Section: Related Workmentioning
confidence: 99%
“…The trust in doctors that patients place and anxiety visiting doctors are additional examples of health-related psychometric dimensions [22,54]. All three of these, and other related dimensions, have been shown to impact future health outcomes including well-being [45]. However, effectively collecting and measuring such covariates in a timely and unobtrusive manner has proven elusive in real-world settings [27].…”
Section: Related Workmentioning
confidence: 99%